Optimization of reaction conditions by detailed cycle simulation of thermo-chemical air separation for high-purity nitrogen production using the perovskite oxide SrFeO3 - Katrin Klingel; Lena Klaas; Nicole Neumann; Mathias Pein; Martin Roeb; Christian Sattler (Chemical Engineering Journal, 2026)

Development and analysis of a SmPC-based machine-readable dataset of contraindications for clinical decision support and real-world data analysis - Miriam Schechner; Wahram Andrikyan; Thomas Bauerdick; Theresa Terstegen; Louisa Redeker; Martin Federbusch; Katrin Farker; Alexander Strübing; Florian Schmidt; Petra Thürmann; Sven Schmiedl; Hanna M. Seidling; et al. (European Journal of Clinical Pharmacology, 2026)
Purpose Unrecognized contraindications pose risks for adverse drug reactions, hospitalizations or death. Clinical decision support systems (CDSS) aim to mitigate medication-related harm, particularly originating from contraindications. However, many CDSS provide limited benefit, as they focus largely on singular risk situations such as drug-drug interactions and often generate alerts of limited clinical relevance. Comprehensive integration of contraindications into CDSS may support more clinically meaningful alerts. The aim of this work was the development and analysis of machine-readable contraindication lists, including drug-clinical condition, drug-kidney function and drug-drug (group) contraindications, for integration into CDSS and real-world data analysis. Methods We extracted and operationalized contraindications, based on Summaries of Product Characteristics (SmPCs), of the 688 most prescribed drugs in Germany, leveraging common medical coding systems. Moreover, we analyzed extracted contraindications based on operationalizability, overall frequency and frequencies within different contraindication categories. Results In total, we extracted 4676 contraindications, of which 2129 (45.5%) were deemed operationalizable. Of these 2129 contraindications, 1652 (77.6%) were attributed to drug-clinical condition, 83 (3.9%) to drug-kidney, 140 (6.6%) to drug-drug group and 254 (11.9%) to drug-drug. The most frequently mentioned contraindicated risk situations were ‘severe liver insufficiency’ ( n = 74, 3.5%), ‘pregnancy’ ( n = 66, 3.1%), ‘MAO-inhibitors’ ( n = 44, 2.1%), and ‘shock’ ( n = 44, 2.1%). Conclusion Our results show, that drug-clinical condition contraindications are listed far more frequently in SmPCs than other contraindication categories. Focusing on clinical condition-related contraindications within CDSS could improve the detection of clinically relevant contraindications in routine data and enhance medication safety. The clinical applicability is currently being evaluated in the INTERPOLAR study.

Collaborative ring trial for the detection of cow, sheep and goat milk in dairy samples by real-time PCR targeting mitochondrial DNA - Kristina Kappel; Maik Döring; Stefan Nöbel; Katrin Neumann; Claudia Brünen-Nieweler; Ingo Krujatz; Bert Pöpping; Kathrin Szabo; Ilka Haase (Journal of Consumer Protection and Food Safety, 2026)
Authentication of dairy product composition is vital for consumer protection and food safety. This study validated 4 real-time PCR methods targeting mitochondrial DNA from cattle, sheep, goat, and total mammals in a collaborative ring trial. Twelve well-characterised dairy samples – including milk, yoghurt, Picodon-type cheese, and Feta-type cheese ‒ were produced from sheep and goat milk with 1–33.3% cow milk admixture for use in a ring trial involving 15 laboratories. Additional samples from various production stages increased the total to 50, which were also analysed by a single laboratory. All 4 real-time PCR assays demonstrated high specificity and sensitivity, with no false positives or negatives observed in the collaborative trial. Quantitative analysis of species proportions showed good precision across laboratories. However, the proportion of cattle DNA was consistently underestimated due to lower somatic cell counts in cow milk. This bias was effectively reduced by calibrating with milk-based reference samples rather than DNA standards. The methods performed reliably across diverse dairy matrices and production stages. Duplex PCR formats matched the performance of singleplex assays while reducing both time and reagent use. Quantitative results support differentiation between economically motivated adulteration and incidental contamination, although precise determination of cow milk admixture remains challenging due to biological variability. The validated real-time PCR methods described in here are included in the Official Collection of Methods of Analysis (ASU), published by the German Federal Office of Consumer Protection and Food Safety (BVL).

Club cell protein (CC16) in serum as an effect marker for small airway epithelial damage caused by diesel exhaust and blasting fumes in potash mining - Savo Neumann; Swaantje Casjens; Frank Hoffmeyer; Katrin Rühle; Lisa Gamrad-Streubel; Lisa-Marie Haase; Katharina K. Rudolph; Jörg Giesen; Volker Neumann; Dirk Taeger; Dirk Pallapies; Thomas Birk; et al. (International Archives of Occupational and Environmental Health, 2024)
Objective The effect marker club cell protein (CC16) is secreted by the epithelium of the small respiratory tract into its lumen and passes into the blood. Increased amounts of CC16 in serum are observed during acute epithelial lung injury due to air pollutants. CC16 in serum was determined as part of this cross-sectional study in underground potash miners on acute and chronic health effects from exposures to diesel exhaust and blasting fumes. Methods Nitrogen oxides, carbon monoxide, and diesel particulate matter were measured in 672 workers at a German potash mining site on a person-by-person basis over an early shift or midday shift, together with CC16 serum concentrations before and after the respective shift. CC16 concentrations and CC16 shift-differences were evaluated with respect to personal exposure measurements and other quantitative variables by Spearman rank correlation coefficients. CC16 shift-differences were modeled using multiple linear regression. Above-ground workers as reference group were compared to the exposed underground workers. Results Serum concentrations of CC16 were influenced by personal characteristics such as age, smoking status, and renal function. Moreover, they showed a circadian rhythm. While no statistically significant effects of work-related exposure on CC16 concentrations were seen in never smokers, such effects were evident in current smokers. Conclusion The small airways of current smokers appeared to be vulnerable to the combination of measured work-related exposures and individual exposure to smoking. Therefore, as health protection of smokers exposed to diesel exhaust and blasting fumes, smoking cessation is strongly recommended.

Impact of diesel exhaust exposure on urinary 1-hydroxypyrene in underground salt and potash workers - Swaantje Casjens; Savo Neumann; Katrin Rühle; Lisa Gamrad-Streubel; Lisa-Marie Haase; Katharina K. Rudolph; Thomas Birk; Jörg Giesen; Volker Neumann; Dirk Pallapies; Jürgen Bünger; Heiko U. Käfferlein; et al. (International Journal of Hygiene and Environmental Health, 2023)

Underground salt and potash workers exposed to nitrogen oxides and diesel exhaust: assessment of specific effect biomarkers - Lisa Gamrad-Streubel; Lisa-Marie Haase; Katharina K. Rudolph; Katrin Rühle; Annette M. Bachand; Lori Crawford; Kenneth A. Mundt; Jürgen Bünger; Dirk Pallapies; Dirk Taeger; Swaantje Casjens; Anja Molkenthin; et al. (International Archives of Occupational and Environmental Health, 2022)
Purpose Occupational exposure limits (OEL) for nitrogen oxides (NO, NO 2 ) and diesel exhaust (EC-DPM) were reassessed by the German authorities in 2016/2017. We performed a clinical cross-sectional study among salt and potash underground workers exposed to these substances at relatively high levels to examine possible indicators of acute effects on workers’ health. Methods We measured post- versus pre-shift differences in cardiovascular, inflammatory, immune, and respiratory effect biomarkers and assessed their associations with personal exposures measured during the same shift. We also compared post- versus pre-shift differences in biomarker levels between exposure groups defined based on work site and job type. Results None of the above-ground workers exceeded the OEL for NO 2 and only 5% exceeded the OEL for EC-DPM exposure. Among underground workers, 33% of miners and 7% underground maintenance workers exceeded the OEL for NO 2 ; the OEL for EC-DPM was exceeded by 56% of miners and 17% of maintenance workers. Some effect biomarkers (thrombocytes, neutrophils, MPO, TNF-α, IgE, FeNO) showed statistically significant differences between pre- versus post-shift measurements; however, there were no consistent associations between pre- and post-shift differences and exposure group or personal exposure measurements during the shift. Conclusions We did not find evidence of associations between workplace exposure to NO, NO 2 or EC-DPM and clinically relevant indicators of acute cardiovascular, inflammatory and immune, or respiratory effects among salt and potash underground workers in Germany.

Collaborative trial validation of a new multiplex real-time PCR to sensitively detect allergenic nuts in food - Hans-Ulrich Waiblinger; Carina Geppert; Daniela Bartsch; Katrin Neumann; Rupert Hochegger; Verena Peterseil; René Koeppel; Jakob Frenzel (Journal of Consumer Protection and Food Safety, 2022)
In this article, we present a multiplex real-time PCR method for a simultaneous, sensitive and specific detection and semi-quantitative estimation of the allergenic species peanut, hazelnut, walnut and cashew in food. Due to the use of multicopy target sequences, a very sensitive detection of the allergenic ingredients was possible. The method was validated in-house as well as by a collaborative trial with 12 laboratories. Within the ring trial, 0.64 mg/kg (i.e. approx. 0.1–0.2 mg of peanut and tree nut-derived protein/kg) could still be detected in a processed cookie matrix, confirmed by results of incurred, processed samples spiked at very low levels between 0.9 and 50 mg/kg of the corresponding allergenic ingredient (peanut, tree nut). In addition, the method revealed good precision data. With regard to quantitative analysis though, insufficient recovery data (bias) were determined in some cases, resulting in measurement uncertainties of more than 50%.

Immune regulation in renal inflammation - Katrin Neumann; Gisa Tiegs (Cell and Tissue Research, 2021)
Renal inflammation, induced by autoantigen recognition or toxic drugs, leads to renal tissue injury and decline in kidney function. Recent studies have demonstrated the crucial role for regulatory T cells in suppressing pathogenic adaptive but also innate immune responses in the inflamed kidney. However, there is also evidence for other immune cell populations with immunosuppressive function in renal inflammation. This review summarizes mechanisms of immune cell regulation in immune-mediated glomerulonephritis and acute and chronic nephrotoxicity.

Import and export of biological samples from tropical countries–considerations and guidelines for research teams - Swen C. Renner; Dirk Neumann; Michael Burkart; Ute Feit; Peter Giere; Andreas Gröger; Axel Paulsch; Cornelia Paulsch; Mario Sterz; Katrin Vohland (Organisms Diversity & Evolution, 2012)